The Influence of Organizational Culture on Employee Performance at Rahadi Oesman Ketapang Airport - Rifki Rosadi; Andityo Pujo Laksana (CV. Rayyan Dwi Bharata, 2022)
Optimum performance improvement is one very important thing to do in a company. Quality and successful performance in achieving a goal is influenced by factors originating from within the company such as the organizational culture within the company. based on the results of observations made at Rahadi Oesman Ketapang Airport it was found that there were employees/airport staff who seemed ignorant and not optimal in doing their jobs. The purpose of this research is to find out whether there is an influence between organizational culture on employee performance and to find out the influence of this variable. This study uses a combination research method. The data sources used are primary data and secondary data related to employee responses, literature reviews, and journals regarding the influence of organizational culture. Data will be analyzed by simple linear regression analysis. The theoretical basis used is management, human resource management, organizational culture, employee performance, and the state civil apparatus. The results of the study show that there is an influence between organizational culture on employee performance at Rahadi Oesman Ketapang Airport. The results of the study also show that the influence of organizational culture on employee performance at Rahadi Oesman Ketapang Airport is 47.9%, while 52.1% is influenced by other variables outside of organizational culture. Employees at Rahadi Oesman Ketapang Airport in carrying out work refer to predetermined SOP.